Utilising of Instagram Application as a Learning Platform to Enhance Teaching and Learning Process among Vocational College Students (International Journal of Creative Future and Heritage (TENIAT), 2025)
ABSTRACT Learning via social media platforms like Instagram is a preferred e-learning approach in modern education, aligning with 21st-century learning. Traditional methods often limit access to resources, reduce motivation, and hinder cognitive and creative growth. Integrating Instagram into technical and vocational courses can enhance learning engagement and effectiveness. This study aims to assess the level of knowledge, identify perceptions, and evaluate students' literacy in using the Instagram application for educational purposes. The study also employed the ADDIE model for research design in developing video products and was conducted in a survey format. A total of 100 respondents were selected through random sampling, and the study findings were analysed using the Statistical Package for the Social Sciences (SPSS) version 25. In this study, the research instrument developed was in the form of a questionnaire, and both face and content validity were assessed implemented. Additionally, the study obtained a reliability value of 0.956, indicating a high level of reliability. The results of the analysis conducted on three aspects namely, knowledge (min=0.82), perception (min=0.74), and literacy (min=0.75)- showed positive and high minimum values. Therefore, the study findings suggest that using the Instagram application can facilitate the teaching and learning process in technical and vocational courses regarding knowledge, perception, and literacy. In conclusion, the results demonstrate that Instagram can enhance teaching and learning processes in technical and vocational courses by increasing engagement, creativity, and cognitive skills. Integrating social media platforms such as Instagram into vocational education can revolutionize teaching strategies and support 21st-century learning goals.ABSTRAK Pembelajaran melalui platform media sosial seperti Instagram adalah pendekatan e-pembelajaran yang semakin digemari dalam pendidikan moden, selari dengan pembelajaran abad ke-21. Kaedah tradisional sering membatasi akses kepada sumber, mengurangkan motivasi, dan menghalang perkembangan kognitif serta kreativiti. Integrasi Instagram dalam kursus teknikal dan vokasional dapat meningkatkan penglibatan dan keberkesanan pembelajaran. Dalam pada itu, pembelajaran abad ke-21 berasaskan media sosial seperti Instagram seharusnya diterapkan dalam proses pengajaran dan pembelajaran bagi kursus teknikal dan vokasional. Kajian ini dijalankan bagi mengkaji tahap pengetahuan, mengenalpasti persepsi dan mengkaji literasi pelajar dalam penggunaan aplikasi Instagram dalam pembelajaran. Kajian ini turut menggunakan model ADDIE bagi reka bentuk kajian dalam pembangunan produk video dan kajian ini berbentuk tinjauan. Jumlah responden adalah seramai 100 orang dengan menggunakan kaedah persampelan secara rawak dan dapatan kajian dianalisis menggunakan perisian Statistical Package for The Social Sciences (SPSS) versi 25. Dalam kajian ini, instrumen kajian yang telah dibangunkan adalah berbentuk soal selidik dimana kesahan antara muka dan juga kesahan kandungan turut dilaksanakan. Selain daripada itu, kajian ini juga memperolehi nilai kebolehpercayaan sebanyak 0.956 dan berada pada tahap yang tinggi. Hasil analisis yang dilakukan terhadap tiga (3) aspek iaitu pengetahuan (min=0.82), persepsi (min=0.74) dan literasi (min=0.75) menunjukkan nilai min yang positif dan tinggi. Oleh itu, dapatan kajian menunjukkan bahawa dengan menggunakan aplikasi Instagram ini mampu memudahkan proses pengajaran dan pembelajaran berdasarkan kursus teknikal dan vokasional menerusi aspek pengetahuan, persepsi dan literasi. Kesimpulannya, aplikasi Instagram boleh meningkatkan proses pengajaran dan pembelajaran dalam kursus teknikal dan vokasional dengan meningkatkan penglibatan, kreativiti, dan kemahiran kognitif. Mengintegrasikan platform media sosial seperti Instagram ke dalam pendidikan vokasional dapat merevolusikan strategi pengajaran dan menyokong matlamat pembelajaran abad ke-21.
Keywords: Instagram; knowledge; literacy; teaching; 21st-century learning